2019
DOI: 10.1186/s40537-018-0167-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge discovery from a more than a decade studies on healthcare Big Data systems: a scientometrics study

Abstract: IntroductionThe increasing development of information and communication technologies (ICT) has brought many achievements for human society and greatly influenced people's lives [1], and it has been adding significant benefits to various aspects of it [2]. Captured and stored huge quantities of information about people, their daily interactions and even their biotic signs via a variety of digital devices, potentially processed and analyzed by academic researchers, corporations, and governments [3]. Fortunately,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The results showed that there is the need to think and plan carefully for big data cycles, simultaneously combining technical aspects with organizational considerations. Data scientists take decisions in some of the phases in the big data cycle that are not neutral in terms of their results [45,46], starting from the selection of data. Data scientists and policy-makers must establish a good dialogue, as only the latter can truly understand the implications of the policies settled upon and the outcome of these policies, or even, and sometimes more critically, those of the negotiations that must be pursued to achieve these policies.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that there is the need to think and plan carefully for big data cycles, simultaneously combining technical aspects with organizational considerations. Data scientists take decisions in some of the phases in the big data cycle that are not neutral in terms of their results [45,46], starting from the selection of data. Data scientists and policy-makers must establish a good dialogue, as only the latter can truly understand the implications of the policies settled upon and the outcome of these policies, or even, and sometimes more critically, those of the negotiations that must be pursued to achieve these policies.…”
Section: Discussionmentioning
confidence: 99%
“…Health is always an interesting field for researchers, and the rapidly expanding field of big data analysis has begun to play a key role in the evolution of medical practices and research [20]. Due to its innovative contribution to decision-making and strategic development in the health sector, Big Data Analytics has attracted considerable attention [21].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The endogenous drivers refer to various influencing factors and conditions arising within the in fields of big data in healthcare and closely affect its operation activities. The logic behind the development motivation, capacity of the public sector and market forces is as follows [11].…”
Section:  Endogenous Driversmentioning
confidence: 99%